The Influence of Dividends Per Share (DPS) and Earnings Per Share (EPS) on Stock Prices in Retail Trade Sector Companies Listed on the Indonesia Stock Exchange for the Period 2016-2022 - Novianto Irdana Ilham; Fanlia Prima Jaya (PT. Hanken Sukses Jaya, 2024)
The aim of this research is to determine the influence of dividends per share and earnings per share on stock prices within the retail trade sub-sector companies listed on the Indonesia Stock Exchange (IDX). This study employs a quantitative research method utilizing secondary data derived from financial documents or reports registered with the Indonesia Stock Exchange (IDX). The research sample consists of 4 companies selected using purposive sampling methods, and the data used comprises seven consecutive years of financial reports from 2016 to 2022. The data analysis techniques utilized include frequency distribution, classical assumption tests, and both partial and multiple linear regression analyses. The results of this research indicate that dividends per share have a significant partial influence on stock prices. Similarly, earnings per share exhibit a significant partial influence on stock prices. Moreover, the simultaneous testing of dividends per share and earnings per share demonstrates a significant combined influence on stock prices.